2018
DOI: 10.1128/mbio.00955-18
|View full text |Cite
|
Sign up to set email alerts
|

Structural Constraints at the Trimer Apex Stabilize the HIV-1 Envelope in a Closed, Antibody-Protected Conformation

Abstract: The human immunodeficiency virus type 1 (HIV-1) envelope (Env) trimer evades antibody recognition by adopting a closed prefusion conformation. Here, we show that two conserved tyrosines (Y173, Y177) within the second variable (V2) loop of the gp120 Env glycoprotein are key regulators of the closed, antibody-protected state of the trimer by establishing intramolecular interaction with the base of the third variable (V3) loop. Mutation of Y177 and/or Y173 to phenylalanine or alanine dramatically altered the susc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(43 citation statements)
references
References 43 publications
1
42
0
Order By: Relevance
“…Despite decades of research, the human immunodeficiency virus (HIV) remains a prominent global issue, with 38 million people estimated to be living with the virus in 2019 [ 1 ]. Targeting the viral envelope glycoprotein, gp120, in vaccine designs has proven to be difficult due to the protein’s extensive glycosylation, frequent mutations, and conformational camouflage of neutralizing epitopes [ 2 , 3 , 4 , 5 , 6 ]. A less commonly discussed feature of the viral envelope that may be of interest when informing new therapeutics or vaccine designs is the myriad of cellular proteins embedded within it.…”
Section: Introductionmentioning
confidence: 99%
“…Despite decades of research, the human immunodeficiency virus (HIV) remains a prominent global issue, with 38 million people estimated to be living with the virus in 2019 [ 1 ]. Targeting the viral envelope glycoprotein, gp120, in vaccine designs has proven to be difficult due to the protein’s extensive glycosylation, frequent mutations, and conformational camouflage of neutralizing epitopes [ 2 , 3 , 4 , 5 , 6 ]. A less commonly discussed feature of the viral envelope that may be of interest when informing new therapeutics or vaccine designs is the myriad of cellular proteins embedded within it.…”
Section: Introductionmentioning
confidence: 99%
“…As V2-apex bnAbs target the closed conformation of the trimer, based on neutralization profile observed, we hypothesized that the most plausible reason for the loss of susceptibility to V2-apex bnAbs was the loss of closed conformation of the Env. In its closed conformation, the Env trimer occludes several immunodominant epitopes that are targeted by non-neutralizing antibodies (non-nAbs) (39, 41). When neutralization profile against several non-nAbs (those targeting CD4-induced epitopes and V3 loop) was assessed, the L184F mutant virus showed relatively higher neutralization susceptibility to non-nAbs.…”
Section: Discussionmentioning
confidence: 99%
“…Substitution of the small side chain of leucine with the bulky non-polar side chain of phenylalanine led to disruption of interprotomer interactions that have been observed to be critical for maintenance of the trimeric apex. Mutations that alter or disrupt interprotomer contacts in Env trimer have been shown to change its susceptibility to several classes of bnAbs (39, 4143). Overall, our results provide information on the role of a rare escape mutation L184F in the viral envelope that led to resistance to bnAbs targeting the V2-apex.…”
Section: Discussionmentioning
confidence: 99%
“…Unliganded Env is normally present in a closed conformation on HIV-infected cells [15]. Advancements in electron microscopy and cryo-tomography have shown that highly conserved epitopes are hidden in the native Env trimer [13,48,49,50,51].…”
Section: Discussionmentioning
confidence: 99%